NO TITLE FOUNDNO TITLE FOUND. (1st March 2022) - Ley, Graham
The foundation of this journal always envisaged a broad and welcoming attitude to diverse studies of the principle of adaptation at work. That shaping principle can be found in the earliest evidence of human activity, and it may be constructive to understand human culture as the product of Homo adaptans.